Fast‐acting insulin aspart in Japanese patients with type 1 diabetes: Faster onset, higher early exposure and greater early glucose‐lowering effect relative to insulin aspart - Shiramoto, Masanari (J Diabetes Investig, 2017)
INTRODUCTION: Fast‐acting insulin aspart (faster aspart) is insulin aspart (IAsp) in a new formulation with two added excipients (niacinamide and L‐arginine) in order to obtain accelerated absorption after subcutaneous dosing. The present study compared the pharmacokinetic/pharmacodynamic characteristics of faster aspart vs IAsp in Japanese patients with type 1 diabetes. MATERIALS AND METHODS: In a randomized, double‐blind, cross‐over design, 43 participants were given faster aspart and IAsp (0.2 U/kg single dose) at two separate dosing visits. Frequent pharmacokinetic blood sampling was carried out, and pharmacodynamics were assessed using an automated euglycemic clamp lasting for a maximum of 12 h after dosing (target 5.5 mmol/L). RESULTS: Faster aspart showed onset of appearance approximately twice‐as‐fast vs IAsp (least squares means: 3.0 vs 7.1 min; estimated treatment difference −4.1 min, 95% confidence interval [CI]: −5.0, −3.2; P < 0.001) and onset of action occurring approximately 5 min earlier (20.2 vs 25.5 min; estimated treatment difference −5.3 min, 95% CI: −8.4, −2.2; P = 0.001). Within the first 30 min post‐dose, both exposure (area under the curve [AUC](IA) (sp,0–30 min)) and glucose‐lowering effect (AUC(GIR) (,0–30 min)) were approximately twofold greater for faster aspart vs IAsp (P < 0.001 and P = 0.002, respectively). Bioavailability of faster aspart was similar to IAsp (AUC(IA) (sp,0‐t); estimated treatment ratio 0.99, 90% CI: 0.96–1.02), whereas the total glucose‐lowering effect (AUC(GIR) (,0–t)) was slightly lower for faster aspart vs IAsp (estimated treatment ratio 0.93, 95% CI: 0.87–0.99, P = 0.020). CONCLUSIONS: Faster aspart showed faster onset, higher early exposure and a greater early glucose‐lowering effect relative to IAsp in Japanese patients with type 1 diabetes, in accordance with previous findings in Caucasian type 1 diabetes patients.